Evaluation of consumer good product through analysis of quality function deployment and quality factors: A study of Horlicks Bangladesh. - Lama, Debendra (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.